Why More Is Required to Address Maine’s Childhood Lead-Poisoning Problem - Littell, David (Maine Policy Review, 2002)
Although largely hidden from the public eye, childhood lead poisoning has been identified as one of Maine’s leading environmental health problems. Recent data show not only that lead-poisoning levels are unacceptably high among Maine’s children, but also that screening rates are lower than recommended by national health organizations and lower than in other New England states. David Littell discusses why childhood lead poisoning is such a problem in Maine and what can be done to remedy the situation, providing a thorough examination of how children are exposed to lead and the magnitude of the problem. He reviews the state’s existing program, and contrasts Maine’s approach with that of several other states. Littell concludes with a series of thoughtful recommendations and argues that the state must do much more if it intends to achieve its policy goal of ending childhood lead poisoning by 2010.